Óleos essenciais de três espécies de myrtaceae:composição química, atividades antioxidante, hemolítica, antitumoral, antiocratoxigênica e citogenotóxica - Santiago, Juliana de Andrade (2015)
The aim of this study was to determine the chemical composition and various biological activities of the essential oils from Melaleuca alternifolia (leaves and fruits), Melaleuca quinquenervia (leaves and fruits), and Backhousia citriodora (leaves). The EOs were extracted through the hydrodistillation technique and chemically characterized by GC/MS and GC-FID. The antitumor tests were performed in five cell lines derived from human tumors: A549, MCF7, HepG2, U251-MG and HT144. The frequency of apoptotic cells was analyzed by fluorescence microscopy; morphological changes through contrast microscopy, and DNA content, in the different phases of the cell cycle, through flow cytometry. In addition, several tests were performed to evaluate the antioxidant activity (ABTS, DPPH, hydroxyl radical, β-carotene/ linoleic acid, TBARS , and phosphomolybdenum complex). Hemolytic activity was evaluated in liquid medium (0.15% Ht) and solid medium. The oils extracted from the leaves were evaluated for inhibition of ochratoxin production by Aspergillus niger and A. carbonarius under two different conditions, 15 to 25°C. The cytogenotoxic effects of the essential oil (EO) from B. citriodora were evaluated on Lactuca sativa, using cytogenetic assays, agarose gel electrophoresis, flow cytometry and TUNEL test. According to chromatographic analysis, the major constituents found in the EO from the leaves of M. alternifolia were γ-terpinene (19.30%) and terpinen-4-ol (56.80%), and the oil from the fruit, ρ-cymene (29.48%) and terpinen-4-ol (61.29%). The EO from M. quinquenervia leaves showed as major constituents the compounds α-pinene (61.37%) and linalool (22.08%) while in the fruits the same compounds have been identified, but in different proportions: α-pinene (34.49%) and linalool (13.72%), plus other components; ρ-cymene (17.99%) and 1,8-cineole (11.24%). In EO from B. citriodora citral was found (91.19%) as the main constituent. Analyzing the antitumor activity, it was observed that the fruit EO from M. alternifolia reduced the percentage of viable cells in 10 and 11% at concentrations of 100 and 200 µg mL-1 , respectively. The EO from B. citriodora induced significant changes in the distribution of neoplastic cell lines in different phases of the cell cycle, in addition to an increase of apoptotic cells and morphological change of the cells. The EO from the leaf of M. alternifolia showed a higher antioxidant activity to the methods phosphomolybdenum (0.84 µg µg-1 ascorbic acid) and hydroxyl (from 9.7% to 58.9%), and were, along with other oils from Melaleuca, ineffective through the other methods. The EO from B. citriodora showed efficient when using the TBARS methods (47.9 to 56.3%) and phosphomolybdenum (0.81 µg µg -1 ascorbic acid). The oil also showed clastogenic and aneugenic effects on L. sativa cells; induced changes in cell cycle and DNA content, in addition to activating the death of the treated cells. It was found that EOs had hemolytic activity at different concentrations to both methods, except the EOs from M. quinquenervia, which did not cause hemolysis in a solid medium. The EOs also induced the reduction of synthesis of ochratoxin by A. carbonarius and A. niger. Thus, the results expand the potential application of essential oils from B. citriodora, M. alternifolia and M. quinquevervia.